2002
DOI: 10.1103/physrevlett.88.038301
|View full text |Cite
|
Sign up to set email alerts
|

Young's Interference of Electrons in Field Emission Patterns

Abstract: We have observed interference fringes of electrons in field emission patterns from multiwalled carbon nanotubes at 60 K. The observed fringe pattern is reproduced by calculations based on the formula of Young's interference of two beams. Three-beam interference has also been detected over short time periods. We discuss the reason why Young's interference appears in the electron emission pattern in accelerating fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
47
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 9 publications
6
47
0
Order By: Relevance
“…Field emission from metallic tips with nanometer sharpness has been introduced some time ago as highly bright and coherent electron source [1][2][3][4][5][6][7][8]. Only recently, pulsed electron sources with high spatio-temporal resolution were realized by laser-induced field emission from such tips [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Field emission from metallic tips with nanometer sharpness has been introduced some time ago as highly bright and coherent electron source [1][2][3][4][5][6][7][8]. Only recently, pulsed electron sources with high spatio-temporal resolution were realized by laser-induced field emission from such tips [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In 1998, we reported that the energy spread of electrons emitted from a superconducting Nb tip is one order of magnitude lower than those of the conventional field emission (FE) tip [1] and nano-scaled tip of carbon nanotubes exhibits large improvement of the spatial coherence length because of the narrow emission area, ∼1 nm [2]. Since the narrowest electron source is a single-atom electron source, Fink fabricated it by remolding techniques [3], and Binh et al developed a surface melting method to construct a nano-protrusion terminated with a single atom [4].…”
Section: Introductionmentioning
confidence: 99%
“…After adsorption of a hydrogen molecule, such symmetries disappear and the field emission patterns change drastically. It is noted that our simulation results are obtained in the very vicinity of CNT tips, without considering any interference in the magnification of current distributions in FEM experiments [12], which is beyond the scope of this study. However, the strong relation between simulated and experimental results supports the previous interpretation of the experiments [3,4] that the bright spots in FEM patterns from CNT tips with adsorbates are of signatures of atom adsorption onto CNTs and the adsorption site should be close to the bright spots.…”
Section: Resultsmentioning
confidence: 98%